The diversity continuum: Blurring the boundaries between internal and external others among Italian children of migrants - Marco Antonsich (2022)
In recent years, studies on nations and nationalism have experienced a rapid growth prompted by the so-called ‘new nationalism’, which has been interpreted, in the Western world, as the product of white majorities and their anxiety towards a demographic change caused by international migration. This article switches focus and explores the impact of demographic change on the nation from the perspective of its non-white population. Using Italy as a case study, the article relies on the voices and online comments of young Italian adults with foreign backgrounds who, like their parents, are often perceived by the white nationalist rhetoric as in need of integration or assimilation. Data rely on 38 individual semi-structured interviews with representatives of ‘second generation’ associations (ReteG2, Associna, Giovani Musulmani d’Italia and Yallaitalia), as well as forums, blogs and videos posted on the webpages of these associations since their creation until June 2015. The article reveals how the existence of an internal other (the Southerner) is discursively mobilised by these young adults to question the ethno-racial unity of the nation and to draw a diversity continuum between their ascribed foreignness and the internal other. This discursive move allows children of migrants to justify their national belonging and to rewrite the nation in relation rather than in opposition to alterity. The relevance of these findings is discussed in terms of the re-making of the nation in times of demographic change and the decline of white majorities.